Andrographolide potentiates the antitumor effect of topotecan in acute myeloid leukemia cells through an intrinsic apoptotic pathway - Hodroj, Mohammad Hassan (2018)
Background Topotecan (TP) is an anticancer drug acting as topoisomerase I inhibitor that is used in the treatment of many types of cancers including leukemia, but it has significant side effects. Andrographolide, a compound extracted from Andrographis paniculata, was recently proven to inhibit the growth of cancer cells and can induce apoptosis. The aim of this study is to investigate the possible synergism between TP and andrographolide in acute myeloid cells in vitro. Materials and methods U937 acute myeloid leukemic cells were cultured using Roswell Park Memorial Institute (RPMI) medium and then treated for 24 h with TP and andrographolide prepared through the dilution of dimethyl sulfoxide (DMSO) stocks with RPMI on the day of treatment. Cell proliferation was assessed using cell proliferation assay upon treatment with both compounds separately and in combination. Cell-cycle study and apoptosis detection were performed by staining the cells with propidium iodide (PI) stain and Annexin V/PI stain, respectively, followed by flow cytometry analysis. Western blotting was used to assess the expression of various proteins involved in apoptotic pathways. Results Both TP and andrographolide showed an antiproliferative effect in a dose-dependent manner when applied on U937 cells separately; however, pretreating the cells with andrographolide before applying TP exhibited a synergistic effect with lower inhibitory concentrations (half-maximal inhibitory concentration). Treating the cells with TP alone led to specific cell-cycle arrest at S phase that was more prominent upon pretreatment combination with andrographolide. Using Annexin V/PI staining to assess the proapoptotic effect following the pretreatment combination showed an increase in the number of apoptotic cells, which was supported by the Western blot results that manifested an upregulation of several proapoptotic proteins expression. Conclusion The pretreatment of U937 with andrographolide followed by low doses of TP showed an enhancement in inducing apoptosis when compared to the application of each compound separately.